Projects-as-Practice: A Deweyan Perspective. Issue 1 (February 2020) - Buchan, Linda; Simpson, Barbara
This article contributes a practice-based approach to project management by opening up to the messiness and unpredictabilities involved in actually doing project work. Drawing on the Pragmatist ideas of John Dewey, we theorize projects-as-practices (noun) and projects-as-practice (verb) as complementary concepts that are built respectively on ontologies of being and becoming . For the purposes of this article, we define the notion of project as an emergent social process of becoming, bounded in time and space, and generative of novel outcomes. We also contribute methodologically by proposing Dewey's Inquiry as a guide to shadowing the bounded becomingness of projects-as-practice (verb). Using an empirical illustration from a Health and Social Care Partnership in Scotland, we highlight the inherently emergent nature of projects as they bring about transformational change.